Valve behavior of the European flat oyster Ostrea edulis and underwater temperature, recorded during a 18-month in situ experiment in Helgoland, Germany - Alexandre Le Moal; Laura Payton; Yannick Geerebaert; Bettina Meyer; Bernadette Pogoda; Damien Tran (PANGAEA, 2025)
This dataset shows the hourly valve behavioral data of the 16 oysters Ostrea edulis throughout the 18 months of the experiment (11th of May 2023 - 31st of August 2024) in Helgoland (Margate) as well as the temperature recorded by the HFNI valvometer. The oyster valve behavior is characterized by 3 parameters: the Valve Opening Amplitude (VOA, the percentage of the valve opening relative to maximum opening), the Valve Opening Duration (VOD, the percentage of time that an oyster spends with its valves open), and the VOA/VOD. The data are presented for each oyster and as a group average. Missing data corresponds to the death of the oyster number 7 or to the stop of recording due to electrical failure on the oyster extquotesingles valvometer electrodes.
In: Le Moal, A et al. (2025): Valve behavior of the European flat oyster Ostrea edulis and associated underwater sound and temperature data, recorded during a 18-month in situ experiment in Helgoland, Germany [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983652